Enzyme-linked immunosorbent assays using recombinant Epstein-Barr virus antigens for detection of nasopharyngeal carcinoma in Malaysian Chinese / Lim Chun Shen - Lim, Chun Shen (2012)
Malaysian Chinese are highly susceptible to Epstein-Barr virus (EBV)-associated nasopharyngeal carcinoma (NPC). Because NPC is often diagnosed at a late stage, accurate EBV serologic tests might be useful to detect NPC in patients with subtle symptoms. And because EBV serological data for Malaysian Chinese are currently lacking, we sought to develop indirect enzyme-linked immunosorbent assays (ELISAs) for a case-control study of NPC in Malaysian Chinese. Of the 165 cases and 658 controls recruited, 89.7% (148/165) prevalent NPC cases were Chinese, in which 14.2% (21/148) Chinese patients were familial NPC cases. The prevalence of family history of NPC among the Chinese controls was 0.6% (2/334), whereas none of the controls of other ethnicity (n = 324) had family history of NPC. Based on individual matching in age and gender, 120 case-control pairs of Chinese descent were selected for the subsequent ELISA study. Using recombinant DNA technology, three EBV proteins: early antigen-diffuse (EA-D), Z-encoded broadly reactive activator (ZEBRA) and viral capsid antigen (VCA) p18, were expressed in and purified from Escherichia coli. The EBV proteins were used as antigens for indirect ELISAs. The antibody levels against the EBV proteins were elevated in NPC cases. Among the serologic tests, the diagnostic accuracy of ZEBRA/IgG (81.7% sensitivity, 61.7% specificity) was the highest, followed by VCA p18/IgG (95.8% sensitivity, 35.0% specificity) and EA-D/IgG (74.2% sensitivity, 48.3% specificity). To serve as useful clinical indicators for NPC, further efforts are needed to improve the accuracies of EBV serologic tests.